An Occupational Choice Model for Developing Countries - Gerardo Jacobs (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
Most occupational choice models introduce only two options for agents: entrepreneurial activities or wage-employment. However, these models represent inadequately the labor force distribution from developing countries, where an important proportion of the total work force are self-employed workers. Some models introduce self-employment as an occupational choice. These works have a common feature : at equilibrium, wage earners belong to the lower end of the income distribution. However, for a large set of developing countries, peasants and small proprietors are part of a self employment sector that can mostly be found in the lower end of the income distribution. In this work, in contrast with previous efforts, self-employment formation is consistent with data from most developing countries. We pay special attention to the conditions under which either the economy ends in a low income equilibrium, where self-employment is the only form of production; or alternatively, a high income equilibrium with a well developed labor market. We study some public policy issues, paying special attention to role of capital markets and the efficiency of schooling.
Keywords: O12; J24; 330; Occupational Choice; Human Capital; Economic Development; General Equilibrium